Diseño de un juego de mesa de estrategias basado en la cultura de la mama negra para difundir la tradición en la colectividad latacungueña en el periodo 2014 - 2015 - Alvarez Veintimilla, Jimsop Franklin (2015)
The investigation aims to transmit to people information on the feast of “Mama Negra”, a tradition of our Latacunga city, known nationally and internationally, however, there is a lack of knowledge about origin and characters of this tradition, so this project is intended to design a board game based on this celebration, to inform the collectivity in a playful manner the cited information. The project used techniques as the survey to a group of students determining the acceptation that will have the board game and the interview with people knowledgeable of the subject who contributed about the tradition of the “Mama Negra”, information that served as support for this project.